The Effects of Sewage Sludge Biochar on Rhizosphere Microbial Community, Soil Quality, and Ryegrass and Cosmos Growth in Pot Culture - Yang Yang; Hongjie Wang; Wenyi Dong; Qitian Li; Qi Han; Chaoxiang Li; Tianhao Liu; Pingyan Zhou (Plants)
Sewage sludge biochar (SSB) is an innovative environmental material with remediation capabilities and significant potential for soil enhancement. This study aimed to accurately assess the dual regulatory effects of SSB on plant growth and soil quality. We conducted potting experiments with ryegrass and cosmos to analyze the impacts of SSB on plant growth, soil quality, and microbial communities. The partial least squares path model (PLS-PM) analysis was employed to elucidate the intrinsic relationships between SSB application and soil environmental factors, microbial communities, and plant growth. The results indicated that the application of SSB significantly enhanced the growth of ryegrass and cosmos, improved the soil quality, and increased the quantity of soil beneficial bacteria in the inter-root soil microbial communities. The addition of 9% and 3% (w w−1) SSB resulted in the most substantial growth of ryegrass and cosmos, with aboveground biomass increasing 68.97% and 68.12%, respectively, and root biomass increasing by 49.87% and 45.14%. PLS path analysis revealed that SSB had a significant effect on the number of bacteria, which also played an important role in soil environmental factors such as pH and conductivity. This study provides a scientific basis for the utilization of sludge resources, green agriculture, and soil improvement. Additionally, it offers technical support for optimizing the application strategy of sludge biochar.